2014
DOI: 10.1111/mmi.12741
|View full text |Cite
|
Sign up to set email alerts
|

Binding of human factor H to outer membrane protein P5 of non‐typeable Haemophilus influenzae contributes to complement resistance

Abstract: Summary Non-typeable Haemophilus influenzae is an opportunistic pathogen of the human upper respiratory tract and is often found to cause inflammatory diseases that include sinusitis, otitis media and exacerbations of chronic obstructive pulmonary disease. To persist in the inflammatory milieu during infection, non-typeable H. influenzae must resist the antimicrobial activity of the human complement system. Here, we used Tn-seq to identify genes important for resistance to complement-mediated killing. This scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 55 publications
(95 reference statements)
2
36
0
1
Order By: Relevance
“…In contrast to Rd, which originally was an encapsulated serotype d strain that lost the capsule, various NTHi strains are constantly under selective pressure for the acquisition of virulence factors that can contribute to serum resistance. Recent studies have shown that NTHi are able to evade IgM binding [31,32] and to scavenge complement inhibitors, C4BP and Factor H [33,34]. The NTHi 375 strain may potentially employ some mechanisms of immune evasion facilitating the observed serum resistance.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to Rd, which originally was an encapsulated serotype d strain that lost the capsule, various NTHi strains are constantly under selective pressure for the acquisition of virulence factors that can contribute to serum resistance. Recent studies have shown that NTHi are able to evade IgM binding [31,32] and to scavenge complement inhibitors, C4BP and Factor H [33,34]. The NTHi 375 strain may potentially employ some mechanisms of immune evasion facilitating the observed serum resistance.…”
Section: Discussionmentioning
confidence: 97%
“…The magnitude of sialic acid-mediated complement resistance differed from strain to strain. Large effects were seen for strains 11P6H, 3655, and 86-028NP, whereas only a modest effect was seen for strain R2866, which might be due to its intrinsic resistance to complement-mediated killing due to other complement evasion mechanisms, such as a complex LOS structure preventing IgM antibody binding and factor H binding to outer membrane protein P5 (10,(20)(21)(22). By measuring incorporation of Neu5Az on the bacterial surface, detected Neu5Az incorporation was high for NTHi strain 11P6H, modest for 86-028NP, and lowest for 3655 and R2866, which supports the largest effect of sialic acid on complement binding and complement-mediated killing of NTHi strain 11P6H.…”
Section: Discussionmentioning
confidence: 98%
“…NTHi bacteria have evolved multiple mechanisms to prevent binding of IgM to its bacterial surface. Outer membrane protein P5, which was also seen to bind human factor H (21,22), was shown to decrease binding of IgM by unknown mechanisms (22). Modification of the LOS was shown to decrease binding of IgM, resulting in lowered complement and opsonophagocytic killing (21,28).…”
Section: Discussionmentioning
confidence: 99%
“…Outer membrane loops 1 and 2 of OmpP5 contribute to the binding of FH via unidentified aa residues. Heterogeneity in these outer membrane loops have been reported and are associated with the levels of FH binding to specific strains (Langereis et al, 2014). …”
Section: Inhibiting the Ap: Fh And Fhl-1mentioning
confidence: 99%